Combination of Ara (Ficus racemosa) and Singkong Leaf (Manihot utillisima) in Cat Fish (Pangasius hypophthalmus) - Rukisah Rukisah; Jimmy Cahyadi; Sukri Faldin (Jurnal Perikanan dan Kelautan, 2020)
One of the problem cultuvation of catfish in the North of Kalimantan is the cost of commercial fish feed in the market is relative expensive. The alternative that can be effort is make feeds by homemade with utilizing local ingredients from nature that is no economi value like fig fruit (F. racemosa) and cassava leaves (M. utillisima) the plants are commonly found in Malinau District. The purpose of the research is to find out the growth of catfish seeds (P. hypophthalmus) by using a combination of  fig fruit (F. racemosa) and cassava leaves (M. utillisima). This research using experimental method, completely randomized design with four treatments and three replications. The data obtained were processed using Analysis of Variance (ANOVA) and continued with  test  least significant difference. The best absolute weight growth of catfish (P. hypophthalmus) at  the treatment D was (1.21 grams), the best absolute length growth at treatment D was (1.09 cm), the best specific growth at the thirty five (0,013%), the best Feed Covertion Ratio for treatment D was (2.11%) and the best Survival Rate for treatment D was (96.67), while the water quality in ammonia on the threatment A was not better than the optimal value 1 mg / L. Combined feed in treatment C is the best treatment compared to treatments A and B, but the combination feed is still unable to produce better growth when compared to treatment D (Commercial).